Correlation in Academic Performance, Purpose in Life and Hopelessness among Final year Medical Students - Butt, Ammara; Iftikhar, Marryam; Mahmood, Zainab (Journal of Fatima Jinnah Medical University, 2023)
Background: Student’s academic performance is the major concern for the educational sector because students are the future practitioners who will serve the society. The academic performance of students is a key feature in teaching. The present study aims to determine the relationship between academic performance, purpose in life and hopelessness among final year MBBS students, by taking hopelessness as predicting variable. Methodology: A Correlational study was conduct at Fatima Jinnah Medical University, Lahore Pakistan. A total no. of 240 final year medical students were included by using convenient sampling technique and they were administered Purpose in Life (PIL) Scale and Beck’s Hopelessness Scale (BHS) along with demographic details. The academic performance of students was measured through 4th year academic scores. Hopelessness was taken as independent variable (IV), while, academic performance and purpose in life served as dependent variables (DVs). Results: The mean age of students was 22.5 years. Results found negative correlation between hopelessness and academic performance (p<0.01), as well as a negative correlation between hopelessness and purpose in life (p <0.01). Hopelessness negatively predicted academic performance (β= -.19, p<.01) and purpose in life (β= -.72, p<.001) among students. Total 25% students were in the normal range of hopelessness, 45.4% students scored in mild range, 23.8% students were in the moderate category, while 5.8% students were found in the severely hopeless category. Conclusion: The study concluded that hopelessness does not only predict purpose in life negatively among students but also affect their academic performance. A wide range of students were found hopeless therefore, various interventions for the prediction of hopelessness in various academic institutes should be made by involving appropriate educational and administrative measures.